Differential Influence of the COVID-19 Pandemic on Mechanical Thrombectomy and Bridging Therapy for Acute Ischemic Stroke - Geng, Dandan; Xu, Xueqian; Luan, Xiaoqian; Qiu, Linan; Chen, Liuzhu; Chen, Jiahao; Wu, Beilan; Xu, Minjie; Ergashev, Akmal; Tang, Wenjie; Li, Jia (Frontiers in Neurology, 2022)
Background:The COVID-19 pandemic is having a dramatic impact on acute stroke care.Its effects may accompany stroke care for a long time. We compared the treatment, short-and long-term functional outcomes of AIS patients from 2019 to 2020.Our objective was to evaluate the effect of COVID-19 epidemic on Mechanical Thrombectomy(MT) in patients in our hospital. Methods:We collected information on subjects who received MT in 2019-2020,including age, sex, time from onset to arterial sheath insertion, time from onset to recanalization,the rate of lung infection and hemorrhagic transformation, modified Rankin scale (mRS),etc. Results:The number of MT patients decreased significantly by 26.6% in 2020( p = 0.025).The pretreatment ASPECTS score for 2020 was significantly higher than that for 2019(p=0.004).Besides,patients were more likely to develop lung infection (65% vs 54.1%, p=0.042), and had a higher risk of hemorrhagic transformation(47.4% vs 30.4%, p=0.005) in 2019.And the discharged mRS refected the much more MT patients in 2019 have a poor short-term functional prognosis (66.0% vs 44.9%, p=0.046).In subgroup analysis of Bridging Thrombolysis(BT), the discharged mRS was observed to reflect the poor short-term functional prognosis of more BT patients in 2020 (62.5% vs 37.5%, P =0.024). However, mRS at 180 days was no difference between 2 years (P =0.094).In addition to ,we compared the treatment effects of direct MT with BT during the COVID-19 epidemic. There was no significant difference in the short and long-term prognosis and mortality. Conclusion:For MT patients, both short-and long-term functional outcomes were not significantly affected due to the mild condition of patients admitted to hospital in 2020.For BT patients, the COVID-19 pandemic has prolonged the green channel time of stroke, leading to poor short-term functional prognosis of stroke patients in the pandemic period.There was no difference in the effectiveness of direct MT and BT during the COVID-19 pandemic.